Studies in budgeting - Byrne, R. F. (Amsterdam : North-Holland Pub. Co., 1971)
This is the second of two volumes projected in a program sponsored by ONR (U.S. Office of Naval Research) and TIMS (The Institute of Management Sciences) to encourage research in "Capital budgeting of interrelated projects".
"Sole distributors for U.S.A.: American Elsevier Publishing Co., New York, N.Y."
Includes bibliographical references p. 377-392.
hza 07/08/2018
Loan
Keywords: Capital investments; Capital budget; Risk; Budget; Program budgeting